Latent Sex Differences in CaMKII-nNOS Signaling That Underlie Antidepressant-Like Effects of Yueju-Ganmaidazao Decoction in the Hippocampus - Yin, Ying; Qian, Shiyu; Chen, Yifan; Sun, Yan; Li, Yuqiao; Yu, Yongfei; Li, Jianqing; Wu, Zhangjie; Yu, Xinlang; Ge, Rui; Han, Jia; Sun, Dongdong; et al. (Frontiers in Behavioral Neuroscience, 2021)
Previous studies have demonstrated that Yueju-Ganmaidazao Decoction (YG) induces rapid antidepressant-like effects, and the antidepressant response is mostly dependent on suppression of NO-cGMP signaling in male mice. This study aimed to investigate the sex difference mediated by CaMKII-nNOS signaling involving in the antidepressant-like effect of YG in mice. We found that the immobility times in the tail suspension test (TST) were decreased after single injection of YG in male and female mice with the same dosage. Additionally, chronic administration for four days of subthreshold dosage of YG and Escitalopram (ES) also significantly decreased the immobility time in mice of both sexes. Chronic subthreshold dosage of YG and ES in LPS-treated mice and in chronic unpredictable stress (CUS) mice both decreased the immobility time which was increased by stress. Meanwhile, in CUS-treated mice, sucrose preference test (SPT), forced swimming test (FST) and open field test (OFT) were applied to further confirm the antidepressant-like effects of YG and ES. Moreover, CUS significantly decreased the expression of nNOS and CaMKII and both YG and ES could enhance the expression in the hippocampus of female mice, which was opposite to that in male mice, while eNOS expression was not affected by stress or drug treatment neither in male mice nor in female mice. Finally, subthreshold dosage of YG combined with 7-nitroindazole (nNOS inhibitor) induced the antidepressant-like effects both in female and male mice while single use of YG or 7-NI did not display any effect. However, pretreatment with KN-93 (CaMKII inhibitor) only blocked the antidepressant-like effect of high dosage YG in female mice. Meanwhile, in CUS mice, chronic stress caused NR1 overexpression and inhibited CREB action, which were both reversed by YG and ES in male and female mice, implying that YG and ES produced the same antidepressant-like effect in mice of both sexes. The study revealed that chronic treatment with a subthreshold dose of YG also produced antidepressant-like effects in female mice and these effects depended on the regulation of the CaMKII-nNOS signaling pathway.